Continuous Decline of Toxoplasma gondii Seroprevalence in Hospital: A 1997–2014 Longitudinal Study in Paris, France - Guigue, Nicolas; Léon, Lucie; Hamane, Samia; Gits-Muselli, Maud; Le Strat, Yann; Alanio, Alexandre; Bretagne, Stéphane (Frontiers in Microbiology, 2018)
Background: The protozoan Toxoplasma gondii presents a risk for reactivation of latent cysts in immunocompromised patients. Anti-T. gondii antibodies are therefore usually screened before chemotherapy or transplantation to propose prophylactic measures against this parasite. We analyzed the results obtained in our hospital to study the epidemiological trend of T. gondii infection. Methods: We collected all the anti-Toxoplasma antibody titers from January 1st, 1997 to December 31st, 2013 using the Platelia IgG ELISA assay (Bio-Rad). The results were classified as positive when titers reached a concentration of ≥10 UI/ml. Only the first result obtained at entry for each patient was considered. T. gondii seroprevalence was estimated using a multivariate logistic regression model accounting for age, sex, and year in which the sample was collected. Results: A total of 21,480 patient samples were analyzed. The seroprevalence continuously decreased over time, from 64.5% in 1997 to 54.7% in 2013 (i.e., an average of 1.3% per year, p<0.001). The decrease was 5.0% per year for patients <20 years. After 2013, the model predicts that the seroprevalence would continuously decrease. We also observed a higher proportion of seropositive men than women in the 15-45 year-old group (58.5% versus 52.0%, p <10-3). Conclusions: The overall seroprevalence of toxoplasmosis at our hospital showed an accelerating downward trend over 17 years. The reason for this continuous decline is likely associated with the lower parasite presence within meat. Thus, although young immunocompromised patients are increasingly less at risk of reactivation in the near future, older immunocompromised patients will remain at high risk of reactivation. The reasons of the higher prevalence in men remain to be explored.